KAJIAN PEMANFAATAN LIMBAH DRILL CUTTING SEBAGAI CAMPURAN AGREGAT PENYUSUN PAVING BLOCK DENGAN METODE SOLIDIFIKASI - Listiani Sari, Liska
Oil and gas drilling process produced not only oil as product but also drill cutting as waste that classified as hazardous waste code D220 in PP 18/1999 jo PP 85/1999. In an effort to minimize potential hazard of waste, there should be a process to convert hazardous waste materials into nonhazardous waste. One kind of common method in treating hazardous waste is solidification. Solidification is one kind of hazardous waste treatment method that aims to reduce hazardous properties of waste by reducing mobility of the pollutant. This study aimed to look direct potential utilization of drill cutting into paving blocks. Drill cutting have characteristics resembles fine aggregate and have potential to replace fine aggregate as substitution materials for concrete block paving. Products made with 3 kinds variation of cement aggregate ratio i.e 1:3, 1:4, 1:5 and 4 kinds variation of waste substitute the aggregates i.e 0%, 20%, 30%, 50%. Parameters observed from specimen designed are compressive strength, Toxicity Characteristic Leaching Procedure and Total Petroleum Hydrocarbon (TPH) of selected specimen, durability and absorption. Highest compressive strength is 205,3 kg/cm2 reached by specimen variation 1:3 20% using drill cutting TPH <1 as its aggregate substitution. This product has met quality standard for paving block B quality. Whereas, lowest compressive strength that still met quality standard for paving block class D is 114,19 kg/cm2 reached by specimen variation 1:3 20% using drill cutting TPH 1-5 as aggregate substitution. All of the specimen have absorption value over 10%. So, none of these specimen have met standard quality for concrete block paving absorption whereas its durability standard fulfilled by all specimen accordance to ASTM 4843.